Atypical antipsychotic treatment in substance induced psychotic disorder: a review - Dankı, Demet; Dilbaz, Nesrin; Okay, Tuncer; Açıkgöz, Çağlar; Bilgin Erdinç, Işıl; Telci, Şükran (Journal of Dependence, 2005)
The risk of diagnosing a comorbid psychiatric disorder among people who abuse or are dependent on any substance is 2.7 times higher than the normal population. The prevalence of a comorbid psychiatric diagnosis varies between 70-75% in psychoactive substance use disorder. The detection of the psychiatric disorder coexisting with substance use disorder is clinically important due to the negative implications on prognosis, treatment approaches and outcome. The rates of diagnosing and treating psychoactive substance induced psychotic disorder are increasing. It is believed that, limbic structures like, mezocortical dopaminergic pathway and nucleus accumbens are the common neuronal pathways that may have a positive reinforcing effect in the development of substance dependence syndrome. The finding that atypical antipsychotics effect this common neuronal pathways resulted in research on use of these drugs ın the treatment of substance dependency. In addition to considering these properties of atypical antipsychotics, other reasons for commonly preferring these drugs in substance induced psychotic disorder are, their selective effect on D2 receptors, positive effects on cognitive functions, their effects on serotonergic and noradrenergic receptors—therefore, their positive effects on mood—their affinity on 5 HT3 receptor which is implicated in substance seeking behavior.This paper aims to review the psychiatric disorders related to substance addiction, the pathophysiology and the clinical features of substance induced psychotic disorder and to discuss the use of atypical antipsychotic medications as a new approach in the treatment of substance dependency through an extensive literature search.
Keywords: Psychoactive substance; psychotic disorder; atypical antipsychotic